Performing Piety in the Digital Sphere: Framing and Visual Mediation in Hawaariyyun’s Islamic Content - Siti Masitho; Ghorbanali Karimzadeh Gharamaleki (Journal of Digital Religion and Contemporary Society, 2026)
This article examines the digital representation of piety in the Islamic content of the @Hawaariyyun account on social media, exploring how it embodies the transformation of piety in the digital age. Through Robert N. Entman’s framing analysis approach and the visual piety perspective, this study explores how Islamic spiritual values are mediated by the visual, algorithmic, and consumptive logic of social media. The results show that @Hawaariyyun frames the spiritual crisis of modern society as a moral problem caused by ego and hedonistic digital culture, and offers solutions in the form of reflective preaching that emphasizes sincerity, simplicity, and self-introspection. The visualization of piety plays a dual role, expanding the space for participatory preaching while placing spirituality within the logic of popularity and media consumption. This article contributes to the development of digital Islam studies by providing a critical framework for understanding piety as a cultural phenomenon that negotiates religious values with media aesthetics and algorithmic influences. These findings enrich the literature on the relationship between religion, gender, and media, and encourage ethical and authentic digital da’wah practices.